O Schopenhauer "romântico" na novela "Eva" do jovem Horkheimer - Zanghi, Daniele (Voluntas: Revista Internacional de Filosofia, 2020)
The purpose of the present paper is to clarify the different ways in which the young Max Horkheimer received Schopenhauer’s philosophy in his early writings Aus der Pubertät. The text analysis reveals that the young Horkheimer adopted during the 1914-1916 period a romantic perspective and a more illuministic one in the 1917-1918 period. This paper specifically focuses on a novel from the first period, Eva, from which it appears that Horkheimer subscribed to Schopenhauer’s doctrine of the aesthetical genius in an original way.